2011
DOI: 10.5194/nhess-11-2021-2011
|View full text |Cite
|
Sign up to set email alerts
|

Detection of electromagnetic anomalies of three earthquakes in Mexico with an improved statistical method

Abstract: Abstract.A method for detecting seismomagnetic signals is presented. This work presents evidence of geomagnetic perturbations associated with three earthquakes (EQs) that occurred in Mexico within a distance of ρ = (1.8) 10 0.45M , where M is the magnitude of the EQ, during the year 2010. An improved statistical analysis in relation with the polarization analysis (as the ratio of vertical magnetic field component to the horizontal one) has been developed. The variation index (S 4 ) shows important differences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 27 publications
2
5
0
Order By: Relevance
“…The period of time analyzed for each event was of 24 hours. The distance between the EQs and the geomagnetic observatory is consistent with that used in previous studies (Chavez et al 2010;Chavez et al 2011). In those studies, the perturbations associated with the magnitude of the EQs could be observed.…”
Section: Ulf Geomagnetic Data and Eqssupporting
confidence: 72%
See 1 more Smart Citation
“…The period of time analyzed for each event was of 24 hours. The distance between the EQs and the geomagnetic observatory is consistent with that used in previous studies (Chavez et al 2010;Chavez et al 2011). In those studies, the perturbations associated with the magnitude of the EQs could be observed.…”
Section: Ulf Geomagnetic Data and Eqssupporting
confidence: 72%
“…This analysis is completed with a statistical method applied to the FFT ULF data observed in Mexico during the years 2009, 2010 and 2011. Significant differences were found for the data obtained in periods of 24 hours with seismic activity and random signals of the same duration with no seismic activity for eight EQs recorded in Mexico near the observing station, considering a distance of r D (1.8) 10 0.45M (Chavez et al 2011), where M is the magnitude of the EQ reported by the Seismological National Service of Mexico.…”
Section: Introductionmentioning
confidence: 82%
“…These results show that the proposed methodology is a suitable tool to find the EM seismic precursors since it detects spikes or frequency components in the signal over time as shown in figures 5(a)À(f). In particular, the main frequency found in the analysed ULF seismomagnetic is around 0.01 Hz, a period of 100 s; however, this main frequency can change depending on the direction, the distance, and the magnitude of each EQ analysed (Chavez et al 2011). Similar periods of the ULF seismo-magnetic phenomena have been reported by Hayakawa et al (1996), Uyeda et al (2002), Hattori (2004), Hattori, Han, Yoshino, et al (2013), Hattori, Han, and Huang (2013), and Han et al (2011Han et al ( , 2014.…”
Section: St-music-based Geomagnetic Wave Analysissupporting
confidence: 68%
“…The analysed signals correspond to geomagnetic signals and EQ events of magnitude M > 5.5 that have occurred from 2008 to 2010. The background magnetic field observations are within the EQ radius preparation zone (p), where p D (1.8)10 0.45M (Chavez et al 2011). The overall characteristics of the seismic events are presented in table 1, which is organized according to the D/p ratio, where D is the distance between the seismic event and the Juriquilla observatory, Queretaro, Mexico, place where the data have been recorded.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, pre-earthquake ionospheric anomalies have drawn intensive attention (Astafyeva and Heki, 2011;Calais and Minster, 1995;Chavez et al, 2011;Dautermann et al, 2007;Hasbi et al, 2011;Kim and Hegai, 1999;Oyama et al, 2008). Earthquake ionospheric effects are becoming a hotspot of earthquake precursor information exploration.…”
Section: Introductionmentioning
confidence: 99%